Kajian Terhadap Cacat Tersembunyi Dalam Perjanjian Jual Beli Benda Bergerak - Bing Waluyo (Faculty of Law, Universitas Wijayakusuma, 2021)
The main obligation of the seller in the sale and purchase agreement is to give up property rights over the object being traded and to bear enjoyment over the object and to bear any hidden defects. In Article 1504 of the Civil Code, namely the seller is obliged to bear hidden defects in the object being sold, which makes the object unable to use the intended use, or thereby reduces the use of it, so that if the buyer finds out about the defect, he will absolutely not buy the item, or will not buy it other than at a lower price. However, determining the size of the existence of a hidden defect in each person will be different, there may be someone who can accept the object he bought, even though according to the opinion of other buyers the object has hidden defects. The existence of hidden defects in the objects purchased can result in losses to the buyer because they do not get the object as expected in accordance with what has been previously agreed between the seller and the buyer, and will have legal consequences for the parties. From these descriptions, it encourages the author to write about a study of hidden defects in the agreement in the sale and purchase of movable objects. The research approach method used is juridical normative, while the research specification used is descriptive analysis.Keywords: Hidden Defects, Movable Objects, Agreements, Sale and Purchase.Â Kewajiban utama penjual dalam perjanjian jual beli adalah menyerahkan hak milik atas benda yang diperjual-belikan dan menanggung kenikmat-tenteraman atas benda tersebut serta menanggung terhadap cacat-cacat yang tersembunyi. Di dalam Pasal 1504 KUH Perdata, yaitu penjual diwajibkan menanggung terhadap cacat tersembunyi pada benda yang dijual, yang membuat benda itu tak sanggup untuk pemakaian yang dimaksud, atau yang demikian mengurangi pemakaian itu, sehingga seandainya si pembeli mengetahui cacat itu, ia sama sekali tidak akan membeli bendanya, atau tidak akan membelinya selain dengan harga yang kurang. Akan tetapi menentukan ukuran adanya cacat tersembunyi pada setiap orang akan berbeda, mungkin ada orang yang dapat menerima benda yang dibelinya itu, walaupun menurut anggapan pembeli lain benda itu terdapat adanya cacat tersembunyi. Adanya cacat tersembunyi pada benda yang dibeli dapat mengakibatkan kerugian pada pembeli karena tidak mendapatkan benda seperti yang diharapkan sesuai dengan apa yang telah diperjanjikan antara penjual dan pembeli sebelumnya, dan akan mempunyai akibat hukum terhadap para pihak. Dari uraian-uraian tersebut, mendorong penulis untuk menulis tentang kajian terhadap cacat tersembunyi dalam perjanjian dalam perjanjian jual beli benda bergerak. Adapun metode pendekatan penelitian yang digunakan adalah yuridis normatif, sedangkan spesifikasi penelitian yang digunakan adalah deskriptif analistis.Kata Kunci: Cacat Tersembunyi, Benda Bergerak, Perjanjian, Jual Beli